Purification and partial characterization of novel penicillin V acylase from Acinetobacter sp AP24 isolated from loktak lake, an indo-burma biodiversity hotspot - Philem, Pushparani Devi; Sonalkar, Vidya V.; Dharne, Mahesh S.; Prabhune, Asmita (Preparative Biochemistry & Biotechnology, 2016)
Members of the bacterial genus Acinetobacter have attracted great attention over the past few decades, on account of their various biotechnological applications and clinical implications. In this study, we are reporting the first experimental penicillin V acylase (PVA) activity from this genus. Penicillin acylases are pharmaceutically important enzymes widely used in the synthesis of semisynthetic beta-lactam antibiotics. The bacterium, identified as Acinetobacter sp. AP24, was isolated from the water of Loktak Lake (Manipur, India), an Indo-Burma biodiversity hotspot. PVA production was increased threefold in an optimized medium with 0.2% sodium glutamate and 1% glucose as nitrogen and carbon sources respectively, after 24hr of fermentation at 28 degrees C and pH 7.0 with shaking at 180rpm. The enzyme was purified to homogeneity by cation-exchange chromatography using SP-sepharose resin. The PVA is a homotetramer with subunit molecular mass of 34 kD. The enzyme was highly specific toward penicillin V with optimal hydrolytic activity at 40 degrees C and pH 7.5. The enzyme was stable from pH 5.0 to 9.0 at 25 degrees C for 2hr. The enzyme retained 75% activity after 1hr of incubation at 40 degrees C at pH 7.5.
Keywords: 6-APA; Acinetobacter; Loktak Lake; Penicillin V acylase

Performance of Aspergillus niger (NCIM 563) phytase based feed supplement for broiler growth and phosphorus excretion - Puppala, Kumar Raja; Buddhiwant, Priyanka G.; Agawane, Sachin B.; Kadam, Avinash S.; Mote, Chandrashekhar S.; Lonkar, Vijaysinh D.; Khire, Jayant M.; Dharne, Mahesh S. (Biocatalysis and Agricultural Biotechnology, 2021)
Despite availability of commercial enzymes, the phytase produced from relatively inexpensive systems with high yields are gaining global attention in the feed industries in post-antibiotic era. We studied A. niger NCIM 563 Phytase produced in solid state fermentation (SSF) derived Koji powder and evaluated its utility in the poultry feed for broiler growth performance and phosphorous (P) excretion. The ability of phytase in the dried powder was estimated to dephytinize the poultry feed under simulated gastric conditions. Poultry feed was formulated using A. niger NCIM 563 phytase followed by a 42 days feed trial on broilers. After supplementation of phytase to the diet, there was a reduction of dietary P, maintained growth performance, skeletal development of broilers and reduced levels of phytic acid and available P in the litter. Extracellular phytase was able to replace up to 0.1% P in poultry feed. Minimal downstream processing a low-cost feed supplement with significant phytase activity could provide added advantage for anti-nutrition free poultry feed.
Keywords: Phosphorus; Phytase; Poultry feed; Solid state fermentation

Poly-gamma-glutamic acid biopolymer: a sleeping giant with diverse applications and unique opportunities for commercialization - Nair, Pranav; Navale, Govinda R.; Dharne, Mahesh S. (Biomass Conversion and Biorefinery, 2023)
Poly-gamma-glutamic acid (gamma-PGA) is a biodegradable, non-toxic, ecofriendly, and non-immunogenic biopolymer. Its phenomenal properties have gained immense attention in the field of regenerative medicine, the food industry, wastewater treatment, and even in 3D printing bio-ink. The gamma-PGA has the potential to replace synthetic non-degradable counterparts, but the main obstacle is the high production cost and lower productivity. Extensive research has been carried out to reduce the production cost by using different waste; however, it is unable to match the commercialization needs. This review focuses on the biosynthetic mechanism of gamma-PGA, its production using the synthetic medium as well as different wastes by L-glutamic acid-dependent and independent microbial strains. Furthermore, various metabolic engineering strategies and the recovery processes for gamma-PGA and their possible applications are discussed. Finally, highlights on the challenges and unique approaches to reduce the production cost and to increase the productivity for commercialization of gamma-PGA are also summarized.
Keywords: Commercialization; Multi-nutritious; Poly-gamma-glutamic acid; Waste valorization